2022
DOI: 10.1029/2022jg006987
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Future Vegetation Changes in the Degraded Frozen Soil and the Entire Tibetan Plateau and Climate Drivers

Abstract: About 99% of the Tibetan Plateau (TP) is covered by frozen soils and degradation of frozen soils will certainly impact TP's ecosystems. Here, we investigate decadal changes of frozen soils and net primary productivity (NPP, representing vegetation) in the degraded frozen soil zones and the TP during 1982–2014 and 2015–2100 using a dynamic vegetation model, historical records and the latest CMIP6 projections, as well as observation‐based soil temperature thresholds. In 1982–2014, degraded permafrost soil zones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…As CO 2 emissions increase in intensity, the patterns of rising temperatures in the four scenarios ranged from weak to strong through SSP126 to SSP245 to SSP370 and, finally, to SSP585. Meanwhile, forecasts of levels of precipitation on the Tibetan Plateau in the future also show an overall increase, suggesting the region's future climate is evolving via warming and humidification [54].…”
Section: Trends Of Suitable Distribution Area Of Fpm Under Four Clima...mentioning
confidence: 99%
“…As CO 2 emissions increase in intensity, the patterns of rising temperatures in the four scenarios ranged from weak to strong through SSP126 to SSP245 to SSP370 and, finally, to SSP585. Meanwhile, forecasts of levels of precipitation on the Tibetan Plateau in the future also show an overall increase, suggesting the region's future climate is evolving via warming and humidification [54].…”
Section: Trends Of Suitable Distribution Area Of Fpm Under Four Clima...mentioning
confidence: 99%
“…This was primarily due to an increase in evapotranspiration induced by upward air temperature (Ta), which finally led to significant reductions in soil moisture and runoff [22][23][24]. Correspondingly, a significant decrease in the vegetation cover and biomass of alpine meadows [25], as well as a decrease in vegetation NPP [26], were found. However, other studies have shown a slowing drought trend in the TP [27][28][29].…”
Section: Introductionmentioning
confidence: 99%